(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
This paper deals with the development of a kind of water-in-oil-in-water (w/o/w) multiple-emulsification method to fabricate the SF drug-loading microspheres. The silk fibroin (SF) microspheres were prepared by using SF as vehicle and dexamethasone sodium phosphate (DSP) as drug model. The surface morphology was observed by SEM, the particle diameter and its distribution were observed with Laser particle sizer. The structure was studied by X-ray diffraction and Fourier transform infrared. The properties of drug release were assessed in vitro. The results showed the average size of microspheres varied from 6.53 &#956m to 68.60 &#956m. The structure of SF drug-loading microspheres had an obviously change compared with pure SF; and the change is the appearance of silk I and silk II structures; and its molecular conformation was &#946-sheet. The average drug-loading varied from 5.32 % to 9.01 %, and the average loading varied from 56.43 % to 99.07 %. The drug-loading and loading efficiency increased with the increase of SF concentration. The drug-loading and loading efficiency differed when the treated organic solvent differed, their order is: isopropanol &#8249 acetone &#8249 ethanol. Drug release of SF drug-loading microspheres: there was a slow release effect when the concentration of SF was 3% or 6%. Moreover, in the experimental condition, there was an obvious burst release of the drug when the SF concentration was 9 % or 12 % or when the treated solvent was ethanol.